2021
DOI: 10.2337/dc20-3150
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Incident Fracture in Older Adults With Type 2 Diabetes: The Framingham Heart Study

Abstract: To identify risk factors for fracture in type 2 diabetes. RESEARCH DESIGN AND METHODSThis prospective study included members of the Framingham Original and Offspring Cohorts. Type 2 diabetes was defined as fasting plasma glucose >125 mg/ dL or use of type 2 diabetes therapy. We used repeated-measures Cox proportional hazards regression to calculate hazard ratios (HRs) and 95% CIs for associations between potential predictors and incidence of fragility fracture. RESULTSParticipants included 793 individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Older patients with T2DM are at a particularly high-risk of CVD [ 21 ]. However, other conditions that can increase the risk of frailty [ 22 ], fracture [ 23 ], and renal failure [ 24 ] also coexist in elderly patients. Although SGLT2i is well-tolerated, there are concerns related to volume depletion by the diuretic effect of SGLT2i that can lead to postural hypotension and syncope, especially in patients with older age.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients with T2DM are at a particularly high-risk of CVD [ 21 ]. However, other conditions that can increase the risk of frailty [ 22 ], fracture [ 23 ], and renal failure [ 24 ] also coexist in elderly patients. Although SGLT2i is well-tolerated, there are concerns related to volume depletion by the diuretic effect of SGLT2i that can lead to postural hypotension and syncope, especially in patients with older age.…”
Section: Discussionmentioning
confidence: 99%
“…This additional prognostic value of lower HGS as a predictor of allcause mortality has been reported across several cohort studies from various geographical regions [51,53,[56][57][58][59][60][61][62][63][64][65][66]. Low HGS also predicts future function in care-seeking and non-care-seeking populations [67][68][69][70][71][72][73][74] as well as falls and osteoporotic fractures among older adults [75][76][77][78][79][80][81][82], with the latter likely being directly related to reported associations with physical strength, functional mobility, and bone mineral density.…”
Section: Introductionmentioning
confidence: 71%
“…57 Moreover, several large-scale population-based cohort studies have also demonstrated the close link between poor glycemic control and fracture risks. 79,80 Although fracture and fracture-related mortality are significantly increased in DM compared to in non-DM, there are still many confounding factors modifying the risk, which included sex, age, rate, fracture sites, study design, and geographical regions. Additionally, as shown above, T1DM has a much higher risk of fracture compared to T2DM.…”
Section: Bone Health and Diabetes Mellitusmentioning
confidence: 99%
“…57 Moreover, several large-scale population-based cohort studies have also demonstrated the close link between poor glycemic control and fracture risks. 79,80…”
Section: Bone Health and Diabetes Mellitusmentioning
confidence: 99%